Pengaruh Latihan Battle Rope dan Push Up terhadap Kemampuan Passing Bawah Bolavoli Siswa SMA Negeri 6 Takalar - Ramli, Ramli; Ihsan, Andi; Usman, Arifuddin; Nawir, Nukhrawi; Hudain, Muh. Adnan (Prodi Pendidikan Jasmani dan Olahraga, 2026)
This study aimed to determine the effect of battle rope and push up training on volleyball underarm passing ability of students at SMA Negeri 6 Takalar and to compare the effectiveness of both training methods. A quantitative approach with pre-experimental pretest-posttest design was employed. The sample consisted of 24 students divided into two groups using match ordinal pairing technique: Group A (battle rope training, n=12) and Group B (push up training, n=12). The training program was implemented over 6 weeks with a frequency of 3 times per week (16 sessions). The measurement instrument used the Brumbach underarm passing test with 20 trials. Data were analyzed using Kolmogorov-Smirnov normality test, Levene homogeneity test, and Welch test (equal variances not assumed). Results showed that the battle rope group experienced a mean improvement from 20.50 to 25.67 (increase of 5.17 points), while the push up group improved from 20.50 to 23.17 (increase of 2.67 points). ANOVA and Welch tests yielded F = 3.068 with significance p = 0.087 > 0.05, indicating no significant difference in effectiveness between both groups. The eta-squared value of 0.063 indicated a small effect size. It was concluded that both training methods provide positive effects on underarm passing ability; however, integration with direct technical passing practice is necessary for more optimal results.